1974
DOI: 10.1037/h0036237
|View full text |Cite
|
Sign up to set email alerts
|

Subgroups among opiate addicts: A typological investigation.

Abstract: To delineate homogenous subgroups among hospitalized opiate addicts, a multivariate correlational clustering technique was applied to the Minnesota Multiphasic Personality Inventory profiles of 1,500 addicts, subdivided into 10 subsamples (5 for each sex) representing four different categories of admission into treatment (civilly committed, volunteers, probationers, prisoners). Within each subsample, two homogeneous and replicable profile types were isolated. Type I (33% of all addicts) showed elevations on Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(32 citation statements)
references
References 23 publications
(23 reference statements)
4
28
0
Order By: Relevance
“…Types 1 and 5 in the present study are similar to the aforementioned primary and secondary psychopathic types reported by Blackburn (1975). However, there also is an overlap between the present five types and those described in standard MMPI codebooks (Gilberstadt & Duker, 1965;Marks & Seeman, 1963) and obtained in previous formal MMPI typological investigations of various abnormal groups (Berzins, Ross, English, & Haley, 1974;Goldstein & Linden, 1969;Hill, Haertzen, & Davis, 1962;Megargee, 1977;Whitelock, Overall, & Patrick, 1971). This state of affairs conforms to Sines' (1966) observation that any given MMPI profile type usually is associated with more than one clinical entity and, conversely, that similarly diagnosed individuals often produce quite different profiles.…”
Section: Drscussronsupporting
confidence: 86%
“…Types 1 and 5 in the present study are similar to the aforementioned primary and secondary psychopathic types reported by Blackburn (1975). However, there also is an overlap between the present five types and those described in standard MMPI codebooks (Gilberstadt & Duker, 1965;Marks & Seeman, 1963) and obtained in previous formal MMPI typological investigations of various abnormal groups (Berzins, Ross, English, & Haley, 1974;Goldstein & Linden, 1969;Hill, Haertzen, & Davis, 1962;Megargee, 1977;Whitelock, Overall, & Patrick, 1971). This state of affairs conforms to Sines' (1966) observation that any given MMPI profile type usually is associated with more than one clinical entity and, conversely, that similarly diagnosed individuals often produce quite different profiles.…”
Section: Drscussronsupporting
confidence: 86%
“…It is interesting to compare the present findings with those of Meyer andMegargee ( 1972), Blackburn ( 1971) and Berzins, et al ( 1974). These investigators used different subjects and clustering methods than those used in the present study and obtained somewhat different results.…”
Section: Discussionmentioning
confidence: 47%
“…More recently, however, investigators have attempted to derive MMPI subtypes among groups of offenders on a completely empirical basis, i.e., based on the use of clustering techniques capable of identifying types through an analysis of the interrelacionships existing among the profiles in a given sample of subjects. Although this approach has been used extensively in several areas of psychological investigation, it has been applied only infrequently to the study of criminal offenders, with the outstanding examples being the research of Meyer and Megargee (1972) using inmates in a federal prison for youthful offenders, Blackburn (1971) using hospitalized psychiatric patients convicted of homicide, and Berzins, Ross, English, and Haley ( 1974) using opiate addicts. As will be discussed below, the MMPI profile types resulting from these studies overlap only partially, suggesting that clustering techniques are potentially useful not only for identifying relatively homogeneous MMPI subgroups within different offender populations, but also for characterizing personality similarities and differences existing between such populations.…”
mentioning
confidence: 99%
“…Psychopathology was assessed in a typological fashion by using a cluster analy sis procedure on patients' MMPI profiles (Berzins et al 1974). Applying Ward's Method 1 using the Clustan Computer Program (Wishart 1975), groups of patients with similar psychopathological characteristics were formed .…”
Section: Methodsmentioning
confidence: 99%